2010
DOI: 10.5051/jpis.2010.40.1.33
|View full text |Cite
|
Sign up to set email alerts
|

The expressions of inflammatory factors and tissue inhibitor of matrix metalloproteinase-2 in human chronic periodontitis with type 2 diabetes mellitus

Abstract: PurposeThe purpose of this study was to observe and quantify the expression of interleukin-4 (IL-4), interferon-γ (IFN-γ), and tissue inhibitor of matrix metalloproteinase-2 (TIMP-2) in the gingival tissue of patients with type 2 diabetes mellitus (DM) and healthy adults with chronic periodontitis.MethodsTwelve patients with type 2 DM and chronic periodontitis (Group 3), twelve patients with chronic periodontitis (Group 2), and twelve healthy individuals (Group 1) were included in the study. Clinical criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
(30 reference statements)
4
16
0
Order By: Relevance
“…Interestingly, studies have suggested that the functional gene polymorphisms of IL‐4 play an important role in the pathogenesis of type 2 DM and its complications 41,42 . At the protein level, Shin et al 43 found no differences in IL‐4 and IFN‐γ levels among patients without diabetes and patients with type 2 diabetes. Conversely, a recent study by our research group 44 using enzyme‐linked immunosorbent assay (ELISA) showed that the GCF of patients with type 2 DM presented higher levels of IFN‐γ, IL‐17, and IL‐23 and lower levels of IL‐4 when compared to patients without diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, studies have suggested that the functional gene polymorphisms of IL‐4 play an important role in the pathogenesis of type 2 DM and its complications 41,42 . At the protein level, Shin et al 43 found no differences in IL‐4 and IFN‐γ levels among patients without diabetes and patients with type 2 diabetes. Conversely, a recent study by our research group 44 using enzyme‐linked immunosorbent assay (ELISA) showed that the GCF of patients with type 2 DM presented higher levels of IFN‐γ, IL‐17, and IL‐23 and lower levels of IL‐4 when compared to patients without diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…Cross-sectional baseline (Sbordone et al 1995) and longitudinal continuation study (Sbordone et al 1998 (Iwamoto et al 2001, Talbert et al 2006, O'Connell et al 2008, Aspriello et al 2011, Passoja et al 2011, lacked information about the clinical periodontal status of the subject groups (Araya et al 2003, Gomes et al 2006, Shin et al 2010 or compared groups with different clinical indices of periodontitis (Bulut et al 2001, Safkan-Seppala et al 2006, Correa et al 2008, Matsumoto et al 2009, Venza et al 2010, Surdacka et al 2011. It is possible to assume that altered local, rather than systemic, mediators may have a more important role in periodontitis; however, evidence of quantitative and qualitative differences in these mediators in patients with diabetes is very inconsistent ( Table 2).…”
Section: Cytokines and Adipokinesmentioning
confidence: 99%
“…Moreover, different degrees of glycemic control were not included in this study. Different studies evaluating cellular or microbiologic and also clinical aspects of periodontal disease in patients with DM2 showed a relationship between worst periodontal condition and worst glycemic control 5,8,11,26 . This discussion could also be done regarding metabolic levels, as previously discussed.…”
Section: Discussionmentioning
confidence: 82%
“…The prevalence of periodontitis in patients with diabetes is estimated to be double or triple that in the normal population, 5 and a bidirectional relationship appears to exist that links both diseases. Hyperglycemia and the resulting advanced glycation end‐product formation is one of several pathways that are thought to lead to the higher amounts of interleukin (IL)‐17, IL‐23, interferon‐γ, IL‐1β, and osteo‐regulators associated with bone resorption, for example, 10,11,26 also modifying subgingival microbiota 8,9 . Altogether, DM2 is strongly and positively correlated with periodontal destruction 5 .…”
Section: Discussionmentioning
confidence: 99%